2019
DOI: 10.21614/chirurgia.114.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Lymph Node Dissection for Papillary Thyroid Cancers: A Decade Experience of a Single Surgical Team

Abstract: Premize: Pacienţii cu operaţii tiroidiene trebuie evaluaţi ecografic preoperator iar în cazul leziunilor suspecte puncţia aspirativă cu ac fin (FNA) trebuie să completeze investigaţiile. În ţările vestice, chirurgii endocrini efectuează de rutină ecografii cervicale. Rolul limfadenectomiei profilactice de compartiment central (LPCC) în cazul carcinoamelor papilare tiroidiene (CPT) rămâne controversat. În anul 2014 am efectuat o schimbare de strategie în tratamentul CPT: introducerea LPCC efectuată pe baza crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The outcomes of the included studies are shown in Table 2. Only two studies did not report the incidence of LRR [27], [30]. Only nine studies reported the incidence of central and lateral locoregional recurrence, with zero incidences reported in four of these studies.…”
Section: Primary Outcomementioning
confidence: 99%
“…The outcomes of the included studies are shown in Table 2. Only two studies did not report the incidence of LRR [27], [30]. Only nine studies reported the incidence of central and lateral locoregional recurrence, with zero incidences reported in four of these studies.…”
Section: Primary Outcomementioning
confidence: 99%
“…Therefore, the detection of thyroid malignancies, including small malignant cancers, has also increased significantly in these last decades. Thyroid cancers and especially papillary thyroid carcinoma (PTC) are the most common endocrine malignancies, with an indolent course in more than 90% of cases 1–5 . Long‐term prognosis for well‐differentiated thyroid cancer, including PTC, is excellent, with survival rates in adults at approximately 92%–98% after 10‐year follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancers and especially papillary thyroid carcinoma (PTC) are the most common endocrine malignancies, with an indolent course in more than 90% of cases. [1][2][3][4][5] Long-term prognosis for well-differentiated thyroid cancer, including PTC, is excellent, with survival rates in adults at approximately 92%-98% after 10-year follow-up. Nonetheless, 5%-10% of these cancers develop local recurrences and nodal metastases, which require further treatment and impair the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prognosis of PTC is good, it is prone to present lymph node (LN) metastases (1)(2)(3). The metastasis rate of central LN is 20-50%, and the rate of lateral LN is 10-30% (4). Ultrasonography (US) is the most widely used tool for detecting metastatic LNs, which can also effectively guide fine-needle aspiration (FNA) for suspicious LNs (5).…”
Section: Introductionmentioning
confidence: 99%